2017
DOI: 10.2527/jas.2017.1475
|View full text |Cite
|
Sign up to set email alerts
|

Association of udder traits with single nucleotide polymorphisms in crossbred Bos indicus–Bos taurus cows1,2

Abstract: The size, support, and health of udders limit the productive life of beef cows, especially those with background, because, in general, such cows have a reputation for problems with udders. Genomic association studies of bovine udder traits have been conducted in dairy cattle and recently in Continental European beef breeds but not in cows with background. The objective of this study was to determine associations of SNP and udder support scores, teat length, and teat diameter in half (Nellore), half (Angus) cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…These findings suggest that these are polygenic traits mainly influenced by distinct genes since there are many genomic regions with small additive effects on teat and udder structure, and that most of these are not commonly shared between the two traits. This is in line with previously reported genetic correlations between the traits ranging from 0.46 to 0.81 [7,8,27], as well as with other GWAS studies that found distinct genes associated with teat and udder score in beef [14] and dairy cattle [9].…”
Section: Gene Annotationsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings suggest that these are polygenic traits mainly influenced by distinct genes since there are many genomic regions with small additive effects on teat and udder structure, and that most of these are not commonly shared between the two traits. This is in line with previously reported genetic correlations between the traits ranging from 0.46 to 0.81 [7,8,27], as well as with other GWAS studies that found distinct genes associated with teat and udder score in beef [14] and dairy cattle [9].…”
Section: Gene Annotationsupporting
confidence: 92%
“…Aoki et al [51] suggest that (in mice, at least) protein tyrosine phosphatases are upregulated both during this proliferation phase of mammary gland and the involution phase, and down regulated during lactation. Regarding udder structure in bovine, PTPRR has been identified as upregulated or significantly associated with udder health and structure [52]. Herring et al [14] found the PTPRR gene in close physical proximity with significant SNPs identified by GWAS for udder support and structure in Angus-Nellore crossbred cows.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…According to previous research, intron mutations may affect the host genes factors and interaction between tran- scription (Van et al, 2003;Fushan et al, 2009). Therefore, we used the online software Jaspar Genereg (http://jaspar.…”
Section: Discussionmentioning
confidence: 99%
“…While Pausch et al had extremely high density genetic data, they relied on bull genotypes and the indirect phenotyping of their daughters, raising external validity concerns. Currently, only one study has directly associated udder traits with cow genotypes, relating beef cow teat length, teat diameter, and a composite "udder support" score to genomic data from the low-density Bovine Illumina50k chip (13). Large-scale studies using genotype imputation from low density SNP arrays may maximize genome coverage and make large sample sizes more practical, but they introduce bias towards population averages and limit researcher ability to detect rare variants (14).…”
Section: Introductionmentioning
confidence: 99%